1996
DOI: 10.1017/s0022215100133468
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillar metastasis from adenocarcinoma of the stomach

Abstract: Metastatic carcinoma of the tonsil is rare with only some 100 cases having been reported in the literature, of which nine have resulted from stomach carcinoma. Tonsillar metastases rarely become apparent before the diagnosis of the primary neoplasm. We describe here the clinical and histopathological findings of a case of unilateral palatine tonsil metastasis as the first sign of a signet-ring cell carcinoma of the stomach. This has not been reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Furthermore, retrograde transportation of tumor cells has been suggested. [274275276277278] Metastasis to the oral cavity mostly occurs in the advanced stage of the disease and indicates widespread disease. The prognosis and treatment depends on the site of primary tumor and degree of metastatic spread.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, retrograde transportation of tumor cells has been suggested. [274275276277278] Metastasis to the oral cavity mostly occurs in the advanced stage of the disease and indicates widespread disease. The prognosis and treatment depends on the site of primary tumor and degree of metastatic spread.…”
Section: Discussionmentioning
confidence: 99%
“…tonsil/BSCNoneNoneCerebellum3 MYamauchi [15], 199574/MMod.Gastrectomy12 MRt. tonsil/BSCNoneNoneLiver1 MBenito [16], 199642/MSig.Chemotherapy0 MLt. tonsil/surgery + chemotherapyUnknownUnknownUnknown2 MSuko [17], 199659/MPorGastrectomy24 MLt.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant melanoma [5], renal cell carcinoma [2], breast carcinoma [6], and lung carcinoma [7] have been described as the most common primaries of tonsillar metastases. Adenocarcinoma of the stomach [8] and carcinoma of the pancreas [9] and seminomas [10] are less common primary sites. Sporadic cases of tonsillar metastasis have been reported from prostate carcinoma [11], gall bladder carcinoma [12], anaplastic thyroid carcinoma [13], Merkel cell carcinoma [14], choriocarcinoma [15], and malignant mesothelioma [16].…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of both sides was not observed. Contradictorily, it had been reported that malignant melanoma metastatic to the tonsil usually manifests bilaterally [2,8]. Of the 11 cases, seven patients had enlarged cervical lymph nodes when the palatine tonsil mass was found, while seven patients had primary lesions with metastatic regional lymph nodes, and one patient had metastatic evidence in the liver, two patients in the lung, three patients in the brain, three patients in bone, two patients in the mediastinum, two patients in the subcutis, and one patient in the axilla.…”
Section: Discussionmentioning
confidence: 99%